Vasculitis as a Major Morbidity Factor in Patients With Partial RAG Deficiency - Christoph B. Geier (Frontiers in Immunology, 2020)
Vasculitis can be a life-threatening complication associated with high mortality and morbidity among patients with primary immunodeficiencies (PIDs), including variants of severe and combined immunodeficiencies ((S)CID). Our understanding of vasculitis in partial defects in recombination activating gene (RAG) deficiency, a prototype of (S)CIDs, is limited with no published systematic evaluation of diagnostic and therapeutic modalities. In this report, we sought to establish the clinical, laboratory features, and treatment outcome of patients with vasculitis due to partial RAG deficiency. Vasculitis was a major complication in eight (13%) of 62 patients in our cohort with partial RAG deficiency with features of infections and immune dysregulation. Vasculitis occurred early in life, often as first sign of disease (50%) and was complicated by significant end organ damage. Viral infections often preceded the onset of predominately non-granulomatous-small vessel vasculitis. Autoantibodies against cytokines (IFN-α, -ω, and IL-12) were detected in a large fraction of the cases tested (80%), whereas the majority of patients were anti-neutrophil cytoplasmic antibodies (ANCA) negative (>80%). Genetic diagnosis of RAG deficiency was delayed up to 2 years from the onset of vasculitis. Clinical cases with sole skin manifestation responded well to first-line steroid treatment, whereas systemic vasculitis with severe end-organ complications required second-line immunosuppression and/or hematopoietic stem cell transplantation (HSCT) for definitive management. In conclusion, our data suggest that vasculitis in partial RAG deficiency is prevalent among patients with partial RAG deficiency and is associated with high morbidity. Therefore, partial RAG deficiency should be included in the differential diagnosis of patients with early-onset systemic vasculitis. Diagnostic serology may be misleading with ANCA negative findings, and search for conventional autoantibodies should be extended to include those targeting cytokines.